Cybercrime in Contemporary Society: An Islamic Worldview on Its Framework, Motivations, and Consequences - alfazari‬‏, Kalil; Mohamed Adnan, Mohamad Azrien; Tengku Kasim, Tengku Sarina Aini (Journal of Islamic Educational Research, 2025)
This article examines cybercrime through a threefold lens: its conceptual framework, underlying motivations, and consequences, with an added emphasis on the Islamic worldview. Using a descriptive-analytical method, the study explores how cybercrime encompassing acts like hacking, data theft, and online fraud is driven by diverse motivations, including economic, psychological, social, technological, political, and sexual factors. Beyond conventional analysis, the study incorporates Islamic reflections on these motivations, highlighting ethical and spiritual dimensions often overlooked in secular discourse. The impacts of cybercrime are categorized into six domains: economic, psychological, social, legal, security, and moral-spiritual consequences. From an Islamic perspective, cybercrime erodes moral consciousness (taqwa), promotes unethical behavior, and disrupts societal harmony. The study stresses the need for comprehensive strategies that integrate legal, technological, and ethical measures, including faith-based digital ethics. This approach contributes to a more holistic understanding of cybercrime in contemporary society.